A historical view: transmountain diversion development in Colorado - Winchester, John N., author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2001)
As the headwaters for seven major rivers, water resources in Colorado have been diverted for use for over 150 years. Transbasin diversions have been developed to move water from one river basin to another, including transmountain diversions, which move water over the continental divide. Transmountain diversions have historically been developed to provide water for irrigated agriculture and municipal purposes. This paper briefly discusses the development of each of Colorado's 30 transmountain diversions between the Colorado, South Platte, Arkansas and Rio Grande river basins, and provides a summary of diversions for recent years.
Transbasin water transfers
Not digitized by CSUL Digital Services.
Presented at the 2001 USCID water management conference, Transbasin water transfers on June 27-30, 2001 in Denver, Colorado.